Impact of biological activated carbon pre-treatment on the hydrophilic fraction of effluent organic matter for mitigating fouling in microfiltration. Issue 17 (2nd September 2018) - Pramanik, Biplob Kumar; Roddick, Felicity A.; Fan, Linhua
ABSTRACT: The hydrophilic (HPI) fraction of effluent organic matter, which has protein and carbohydrate contents, has a high propensity to foul low-pressure membranes. Biological activated carbon (BAC) filtration was examined as a pre-treatment for reducing the fouling of a microfiltration (MF) membrane (0.1 µm PVDF) by the HPI organic fraction extracted from a biologically treated secondary effluent (BTSE). Although the BAC removed less dissolved organic carbon, carbohydrate and protein from the HPI fraction than the granular activated carbon treatment which was used for comparison, it led to better improvement in permeate flux. This was shown to be due to the removal/breakdown of the HPI fraction resulting in less deposition of these organics on the membrane, many components of which are high molecular weight biopolymers (such as protein and carbohydrate molecules) through biodegradation and adsorption of those molecules on the biofilm and activated carbon. This study established the potential of BAC pre-treatment for reducing the HPI fouling of the membrane and thus improving the performance for the MF of BTSE for water reclamation.